Spectrophotometric Studies, Synthesis, and Magnetic Properties of Co(II), Cu(II), Ni(II) and UO2(VI) Complexes of 1,2-O-Isopropylidene-4-aza-7-aminoheptane - Şekerci, M. (IAPC Nauka/Interperiodica, 2000)
1,2-O-isopropylidene-4-aza-7-aminoheptane (L) has been synthesized starting from 1-chloro-2,3-O-isopropylidenepropane, which has been prepared from the epichlorohydrine and acetone. Then, the complexes of this ligand with Ni(II), Co(II), Cu(II) and UO2(VI) salts were prepared. The structure of the ligand in its complexes is proposed according to the 1H and 13C NMR, IR, elemental analysis and magnetic susceptibility measurements, thermogravimetric analyses (TGA), and differential thermal analyses (DTA).